THE EFFECT OF TRANSPARENCY AND VILLAGE FUND ALLOCATION ON VILLAGE ECONOMIC GROWTH - Rahmi Raihan (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of transparency and village fund allocation on village economic growth. The research was conducted in Pidie District using a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS). The sample consisted of 325 respondents selected through purposive sampling, representing beneficiaries of village funds. The results show that village fund allocation has a positive and significant effect on village economic growth, while transparency does not have a significant effect. These findings indicate that the success of rural economic development depends greatly on strategic and effective fund allocation. Although transparency is important, it does not directly contribute to economic growth unless accompanied by accountability and effective fund management. Therefore, a combination of strategic financial allocation, transparency, and community participation is essential for promoting sustainable village economic growth.